THE ROLE OF METABOLIC SURGERY FOR PATIENTS WITH OBESITY GRADE I AND TYPE 2 DIABETES NOT CONTROLLED CLINICALLY - CAMPOS,Josemberg (2016)
ABSTRACT Introduction Even considering the advance of the medical treatment in the last 20 years with new and more effective drugs, the outcomes are still disappointing as the control of obesity and type 2 Diabetes Mellitus (T2DM) with a large number of patients under the medical treatment still not reaching the desired outcomes. Objective: To present a Metabolic Risk Score to better guide the surgical indication for T2DM patients with body mass index (BMI) where surgery for obesity is still controversial. Method: Research was conducted in Pubmed, Medline, Pubmed Central, Scielo and Lilacs between 2003-2015 correlating headings: metabolic surgery, obesity and type 2 diabetes mellitus. In addition, representatives of the societies involved, as an expert panel, issued opinions. Results: Forty-five related articles were analyzed by evidence-based medicine criteria. Grouped opinions sought to answer the following questions: Why metabolic and not bariatric surgery?; Mechanisms involved in glycemic control; BMI as a single criterion for surgical indication for uncontrolled T2DM; Results of metabolic surgery studies in BMI<35 kg/m2; Safety of metabolic surgery in patients with BMI<35 kg/m2; Long-term effects of surgery in patients with baseline BMI<35 kg/m2 and Proposal for a Metabolic Risk Score. Conclusion: Metabolic surgery has well-defined mechanisms of action both in experimental and human studies. Gastrointestinal interventions in T2DM patients with IMC≤35 kg/m2 has similar safety and efficacy when compared to groups with greater BMIs, leading to the improvement of diabetes in a superior manner than clinical treatment and lifestyle changes, in part through weight loss independent mechanisms . There is no correlation between baseline BMI and weight loss in the long term with the success rate after any surgical treatment. Gastrointestinal surgery treatment may be an option for patients with T2DM without adequate clinical control, with a BMI between 30 and 35, after thorough evaluation following the parameters detailed in Metabolic Risk Score defined by the surgical societies. Roux-en-Y gastric bypass (RYGB), because of its well known safety and efficacy and longer follow-up studies, is the main surgical technique indicated for patients eligible for surgery through the Metabolic Risk Score. The vertical sleeve gastrectomy may be considered if there is an absolute contraindication for the RYGB. T2DM patients should be evaluated by the multiprofessional team that will assess surgical eligibility, preoperative work up, follow up and long term monitoring for micro and macrovascular complications.